Immunotherapy for Hepatocellular Carcinoma: Current Advances and Future Expectations. (26th March 2018) - Xie, Yingjun; Xiang, Yien; Sheng, Jiyao; Zhang, Dan; Yao, Xiaoxiao; Yang, Yongsheng; Zhang, Xuewen
Abstract : Primary liver cancer is a common kind of digestive cancers with high malignancy, causing 745, 500 deaths each year. Hepatocellular carcinoma is the major pathological type of primary liver cancer. Traditional treatment methods for patients with hepatocellular carcinoma have shown poor efficacy in killing residual cancer cells for a long time. In recent years, tumor immunotherapy has emerged as a promising method owing to its safety and efficacy with respect to delaying the progression of advanced tumors and protecting postoperative patients against tumor relapse and metastasis. Immune tolerance and suppression in tumor microenvironments are the theoretical basis of immunotherapy. Adoptive cell therapy functions by stimulating and cultivating autologous lymphocytes ex vivo and then reinfusing them into the patient to kill cancer cells. Cancer vaccination is performed using antigenic substances to activate tumor-specific immune responses. Immune checkpoint inhibitors can reactivate tumor-specific T cells and develop an antitumor effect by suppressing checkpoint-mediated signaling. Oncolytic viruses may selectively replicate in tumor cells and cause lysis without harming normal tissues. Here, we briefly introduce the mechanism of immunosuppression in hepatocellular carcinoma and summarize the rationale of the four major immunotherapeutic approaches with their current advances.